A Novel Point Mutation of the Splicing Donor Site in the Intron 2 of the Plasmin Inhibitor Gene - Yoshinaga, Haruhiko; Hirosawa, Shinsaku; Chung, Dong Hui; Miyasaka, Nobuyuki; Aoki, Nobuo; Favier, Remi (Thrombosis and Haemostasis, 2000)
Plasmin inhibitor (PI) is a major physiological inhibitor of plasminmediated fibrinolysis; hence, its deficiency results in a severe haemorrhagic diathesis. We analyzed the PI gene of a French boy apparently homozygous for PI deficiency and his heterozygous parents. Both alleles of the homozygous patient had a novel G to A transition at the consensus splicing donor site in the intron 2 of the PI gene. In an expression assay using the heterologous cells transfected with the mutant PI expression vector, 3 types of aberrant transcripts using a cryptic splicing donor site within the intron 2 were detected. All of these mRNAs had a stop codon upstream of the cryptic splicing site and encode only 25 amino acids, comprising the first 21 amino acids of the signal peptide (27 amino acids) plus 4 new amino acids. This mutant was designated as PI-Paris-Trousseau.
Keywords: Plasmin inhibitor; mutation; fibrinolysis; splicing donor site